2021
DOI: 10.7717/peerj.12061
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of international medical students enrolled in Chinese medical institutions towards online teaching during the COVID-19 pandemic

Abstract: Introduction . The COVID-19 pandemic has forced the world to pause. One hundred and eighty-eight countries have imposed countrywide school closures, affecting more than 1.5 billion children and youths. The majority of academic leaders are currently encouraging online education to resolve this crisis. This study aimed to investigate international medical students’ (IMS) experiences of online teaching during the COVID-19 pandemic. Methods Data were collected online using a validated questionnaire and one open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 45 publications
3
25
0
3
Order By: Relevance
“…This study revealed that the mode of online teaching and learning, while having a few positive features such as flexibility in study time, was a poor substitute for learning in a traditional classroom setting. This is in consonance with the findings of recent studies showing that the majority of international medical students were dissatisfied with online classes at Chinese universities [ 73 , 74 ]. Before China allows its international medical students back for face-to-face learning, hosting institutions should attach importance to enhancing the quality of their online teaching [ 74 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study revealed that the mode of online teaching and learning, while having a few positive features such as flexibility in study time, was a poor substitute for learning in a traditional classroom setting. This is in consonance with the findings of recent studies showing that the majority of international medical students were dissatisfied with online classes at Chinese universities [ 73 , 74 ]. Before China allows its international medical students back for face-to-face learning, hosting institutions should attach importance to enhancing the quality of their online teaching [ 74 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is in consonance with the findings of recent studies showing that the majority of international medical students were dissatisfied with online classes at Chinese universities [ 73 , 74 ]. Before China allows its international medical students back for face-to-face learning, hosting institutions should attach importance to enhancing the quality of their online teaching [ 74 ].…”
Section: Discussionsupporting
confidence: 92%
“…These barriers have also been identified in other studies [ 20 , 23 , 28 – 31 ]. For instance, in a study conducted among international medical students in China, poor internet connectivity was cited as a major challenge the students and some faculty encountered during their online sessions [ 32 ] Moreso, studies in high-income economies have reported similar challenges regarding students online learning [ 31 , 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has affected governments globally, and societies are experiencing an odd situation; after the global pandemic, this situation led to a global crisis that touched the aspect of our lives, including family, education, health, work, and the relationship between leaders and followers in our society (Hinojosa et al, 2020 ; Aslam et al, 2021 ; Parveen et al, 2022a ). Organization leaders play a critical role in framing employee experiences at the workplace during and after the pandemic as they adapt to work on new realities (Ngoma et al, 2021 ).…”
Section: Covid-19 and Leadershipmentioning
confidence: 99%